Perspectives on competency-based feedback for training non-specialists to deliver psychological interventions: multi-site qualitative study of the EQUIP competency-based approach - Elnasseh, Abdelrhman; Mehta, Varun S; Manolova, Gergana; Pedersen, Gloria A; Golden, Shannon; Eloul, Liyam; Gebrekristos, Frezgi; Collins, Pamela Y; Mutavi, Teresia; Mbwayo, Anne W; Mathai, Muthoni; Concepcion, Tessa; et al. (Cambridge University Press, 2024)
Abstract Background The use of feedback to address gaps and reinforce skills is a key component of successful competency-based mental health and psychosocial support intervention training approaches. Competency-based feedback during training and supervision for personnel delivering psychological interventions is vital for safe and effective care. Aims For non-specialists trained in low-resource settings, there is a lack of standardised feedback systems. This study explores perspectives on competency-based feedback, using structured role-plays that are featured on the Ensuring Quality in Psychosocial and Mental Health Care (EQUIP) platform developed by the World Health Organization and United Nations Children’s Fund. Method Qualitative data were collected from supervisors, trainers and trainees from multiple EQUIP training sites (Ethiopia, Kenya, Lebanon, Peru and Uganda), from 18 key informant interviews and five focus group discussions (N = 41 participants). Qualitative analysis was conducted in Dedoose, using a codebook with deductively and inductively developed themes. Results Four main themes demonstrated how a competency-based structure enhanced the feedback process: (a) competency-based feedback was personalised and goal-specific, (b) competency-based feedback supported a feedback loop, (c) competency-based feedback supported a comfortable and objective feedback environment, and (d) competency-based feedback created greater opportunities for flexibility in training and supervision. Conclusions A better understanding of the role of feedback supports the implementation of competency-based training that is systematic and effective for trainers and supervisors, which ultimately benefits the learning process for trainees.
Keywords: Education and training; transcultural psychiatry; qualitative research; psychosocial interventions; low- and middle-income countries